Humic Acid and Water Management to Decrease Ferro (Fe2+) Solution and Increase Productivity of Established New Rice Field - . Herviyanti; Teguh Budi Prasetyo; Fachri Ahmad; Amrizal Saidi (JOURNAL OF TROPICAL SOILS, 2012)
The purpose of this research was to gain a technological breakthrough in controlling Fe toxicity (Fe2+) on Ultisol in a new established rice field by using humic acid from rice straw compost and water management, so that optimal production of rice plants could be achieved. The experiment was designed using a 2 × 4 factorials with 3 replications in a split plot design. The main plot was water management consists of 2 levels: continuous and intermittent irrigation (2 weeks flooded and 2 weeks field capacity). Small plot was humic acid which was extracted from rice straw compost by NaOH 0.5 N which consists of 4 levels: 0, 200, 400, and 600 mg kg-1.  The results showed that applications of humic acid from 0 to 600 mg kg-1 that was followed by 2 weeks of intermittent irrigation decreased Fe2+ concentration. It was approaching levels that were not toxic to plants, with soil Fe2+ between 180-250 mg kg-1. The best treatment was found at the application of 600 mg kg-1 humic acid extracted from rice straw compost combined with 2 week flooded – 2 weeks field capacity of water management. Those treatment decreased Fe2+ concentration from 1,614 to 180 mg kg-1 and increased the dry weight of grain from 5.15 to 16.73 g pot-1 compared to continuous flooding and without humic acid application.